2012
DOI: 10.1021/jp302578b
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Field Emission Properties of Electrochemically Synthesized Self-Aligned Nitrogen-Doped TiO2 Nanotube Array Thin Films

Abstract: Vertically aligned TiO 2-δ and TiO 2−3yN2y nanotube array thin films were synthesized electrochemically in a single step. N-Doping at different levels was achieved by using different concentrations of urea, as nitrogen precursor, in the electrolyte. The GIXRD and Raman studies revealed that the nanotube arrays are of anatase phase. The field emission measurements showed low turn-on fields of 10, 9.21, and 6.54 V/μm at 3.88, 4.12, and 4.74 at% of N-doping, respectively, implying enhanced field emission upon N-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 62 publications
2
29
1
Order By: Relevance
“…6 shows the XPS spectra of N1s core levels registered for titania nanotubes doped by using triethyleneamine, diethylenetriamine, ethylenediamine and urea respectively. 34 According to He et al 27 nitrogen may also coordinate to the surface of titania. N1sA, N1sB and N1sC, implying the existence of three different types of N states in all doped samples.…”
Section: Resultsmentioning
confidence: 99%
“…6 shows the XPS spectra of N1s core levels registered for titania nanotubes doped by using triethyleneamine, diethylenetriamine, ethylenediamine and urea respectively. 34 According to He et al 27 nitrogen may also coordinate to the surface of titania. N1sA, N1sB and N1sC, implying the existence of three different types of N states in all doped samples.…”
Section: Resultsmentioning
confidence: 99%
“…The results indicated that the visible light absorption and photoelectrochemical activities of these doped crystallized TNAs were not only influenced by the energy gaps and the distributions of impurity states but were also affected by the locations of Femi levels and the energies of band gap edges [50,51]. Among all these anions, the doping of TNAs with nitrogen or carbon has been found to receive significant attention [52][53][54][55][56][57][58][59]. Highly promising N-doping approach for TNAs includes one-step direct electrochemical anodization of a TiN alloy or growing TNAs in a solution containing doping species [59].…”
Section: Modification Of Tnamentioning
confidence: 99%
“…The unique sp 3 -bonded crystal structure and the low work function of SiNWs show it to be a potential candidate to be employed as a cold cathode material for¯eld emission device applications. 7,8 Over past few years, many other nanomaterials, such as aligned carbon nanotubes, 10 ultra-nanocrystalline diamond lms, [11][12][13] arrays of gallium nitride nanorods, 14 titanium dioxide nanotubes, 15 cone-shaped zinc oxide nanostructures, 16 tin oxide nanotubes 17 and needle-shaped molybdenum trioxide 18 are showing much more e±ciency in¯eld emission with very low turn-on¯eld. Moreover ion implantation, 19 metallic coating 20 and H 2 surface treatment on diamond lms 21 are observed to signi¯cantly enhance the electron¯eld emission (EFE) properties.…”
Section: Introductionmentioning
confidence: 99%